The moral foundations of society and technological progress of the economy in the work of Wilhelm Röpke - Resico, Marcelo Fernando (2018)
Fil: Resico, Marcelo Fernando. Pontificia Universidad Católica Argentina. Facultad de Ciencias Económicas. Departamento de Investigación Francisco Valsecchi; Argentina